2021
DOI: 10.1002/jcla.23989
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunction of miR‐802 in tumors

Abstract: MicroRNAs (miRNAs) are a class of small ribonucleic acids (19-24 nucleotides). 1 miRNAs play an important role in post-transcriptional gene silencing (PTGS). 1 Thousands of miRNAs have been discovered, and they can regulate more than 30% of gene expression. 2 The miR-NAs can be detected in about 50% of the mutated regions in tumor tissues, suggesting that miRNAs may be closely related to the occurrence and development of tumors. 2MicroRNA-802 (miR-802) gene is located on chromosome 21, and its precursor can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…And in the study of bladder cancer and JAK/STAT signaling pathway, IGF family-related genes were found to activate JAK/STAT signaling pathway to proliferate tumors 39 . In the A recent study on IGFL2 found that miR-802 is a tumor growth suppressor and the long-stranded non-coding RNA of IGFL2 (IGFL2-AS1) can promote the progression of gastric cancer by inhibiting the expression of miR-802 40,41 , while in breast cancer studies, IGFL2-AS1 acts as a factor mediating the KLF5/IGFL1 axis and inhibits miR4795-3p expression thereby affecting breast cancer proliferation 42 . Cen et al found a significant decrease in proliferation of COAD cells after knocking down IGFL2-AS1 43 .…”
Section: Discussionmentioning
confidence: 99%
“…And in the study of bladder cancer and JAK/STAT signaling pathway, IGF family-related genes were found to activate JAK/STAT signaling pathway to proliferate tumors 39 . In the A recent study on IGFL2 found that miR-802 is a tumor growth suppressor and the long-stranded non-coding RNA of IGFL2 (IGFL2-AS1) can promote the progression of gastric cancer by inhibiting the expression of miR-802 40,41 , while in breast cancer studies, IGFL2-AS1 acts as a factor mediating the KLF5/IGFL1 axis and inhibits miR4795-3p expression thereby affecting breast cancer proliferation 42 . Cen et al found a significant decrease in proliferation of COAD cells after knocking down IGFL2-AS1 43 .…”
Section: Discussionmentioning
confidence: 99%
“… 143 miR-802 Modulates the regulation of the Wnt, PI3K/AKT, ERK, and Hedgehog signaling pathways. 144 AEG-1, astrocyte elevated gene 1; AKT, protein kinase B; APC, adenomatous polyposis coli; BCL2, B-cell lymphoma 2; CCND1, cyclin D1; CDK6, cyclin dependent kinase 6; EGFR, epidermal growth factor receptor; ERK, extracellular receptor kinase; FOX, forkhead box; GSK3β, glycogen synthase kinase-3β; HIF1, hypoxia-inducible factor 1; IGF-1R, insulin-like growth factor 1 receptor; JAK, Janus kinase; MAPK, mitogen-activated protein kinase; MCL1, induced myeloid leukemia cell differentiation protein; miRNA, microRNA; mTOR, mammalian target of rapamycin; NF-κB, nuclear factor-kappa B; PDCD4, programmed cell death protein 4; PDK1, phosphoinositide-dependent kinase-1; PI3K, phosphatidylinositol 3-kinase; PTEN, phosphatase and tensin homolog; Ras, rat sarcoma virus; RB, retinoblastoma-like protein; RECK, reversion-inducing cysteine-rich protein with Kazal motifs; Smad, small mother against decapentaplegic; Src, steroid receptor coactivator; STAT, signal transducer activator of transcription; TAK1, TGF-β activated kinase 1; TGF-β, transforming growth factor-β; VEGF, vascular endothelial growth factor; XRCC2, X-ray repair complementing defective repair gene; YAP, yes-associated protein. …”
Section: Are Mirnas Involved In the Pathogenesis Of Diabetes Mellitus...mentioning
confidence: 99%
“… 143 hsa-miR-802 Increased 57 Reduced in gastric, colorectal, breast, cervical, and epithelial ovarian cancers, as well as in melanoma and tongue, oral, esophageal carcinoma, and laryngeal squamous cell carcinomas. 144 Increased in hepatocellular carcinoma, bladder urothelial cancer, osteosarcoma, and cholesteatoma tissue cells. 144 miRNA, microRNA.…”
Section: Are Mirnas Involved In the Pathogenesis Of Diabetes Mellitus...mentioning
confidence: 99%
See 1 more Smart Citation
“…A study in breast cancer has demonstrated that miR-802 inhibits proliferation through the suppression of FoxM1 27 . Regarding the prognostic value of miR-802, it is reported that patients with hepatocellular carcinoma and prostate cancer that have lower expression of miR-802 showed better survival 28 . Despite the researches for determining miR-802 roles, there are not enough reports about the roles of miR-802 in the molecular basis of diseases and its clinical potential in malignancies as well as breast cancer.…”
Section: Introductionmentioning
confidence: 99%